Chip Implementation of Two New VCII-Based Voltage/Transimpedance-Mode KHN-Equivalent Biquads - Hua-Pin Chen; San-Fu Wang; Ming-Jin-Yu; Liang-Yen Chen; Yu-Hsi Chen (IEEE Access)
This paper presents two new VCII-based Kerwin-Huelsman-Newcomb (KHN) equivalent biquad circuits, each comprising three second-generation voltage conveyors (VCIIs), two grounded capacitors, and five resistors. Either voltage mode (VM) or trans-impedance mode (TIM) can operate in each proposed circuit configuration. Transfer function analysis using a VM inverting bandpass (IBP) filter yields two additional non-inverting/inverting KHN biquad transfer functions for the two proposed VM/TIM KHN-equivalent biquads. The first proposed VM/TIM KHN-equivalent biquad can simultaneously implement an IBP filter, a non-inverting low-pass (NLP) filter, and an inverting high-pass (IHP) filter. In contrast, the second proposed VM/TIM KHN-equivalent biquad can simultaneously implement an IBP filter, an inverting low-pass (ILP) filter, and a non-inverting high-pass (NHP) filter. Each proposed VM/TIM KHN-equivalent biquad features three low-impedance voltage outputs in the designed circuit, eliminating the need for additional voltage buffers (VBs) in the circuit measurements. The two proposed KHN-equivalent biquads are integrated into a single chip, occupying a total area of 1.44 mm2. This technology uses the TSMC $0.18~μ $ m 1P6M CMOS process, with the chip operating at a supply voltage of ±0.9 V. The measured power dissipation of the first KHN-equivalent biquad is 2.7 mW, while the measured power dissipation of the second one is 3.24 mW. The measured spurious-free dynamic range (SFDR) of the first KHN-equivalent biquad is 41.18 dBc, while the measured SFDR of the second one is 40.94 dBc. With an input voltage of 1.2 Vpp, the measured total harmonic distortion (THD) values for both KHN-equivalent biquads are below 1 %. The proposed two KHN-equivalent biquads have the advantages of high density, system integration, efficiency, low cost, low power consumption, and effective utilization of chip layout area. Simulations and on-chip measurements are carried out for both KHN-equivalent biquads to validate the theoretical design and demonstrate their on-chip feasibility.